Perancangan Dokumen SNI ISO 9001:2015 di PT. X - Evelyn Fabriane; Jani Rahardjo (Jurnal Titra, 2023)
This company is a well-known field of Rotogravure Cylinder Printing with the vision of providing products with the number one quality and service in Indonesia. This final project was carried out because the company did not yet have a quality management system in the production process so that it could expand the market and gain customer trust. Therefore, it is necessary todesign documents for SNI ISO 9001:2015 to facilitate product quality management systems according to standards. Based on the completeness of company’s documents, an initial gap of only 8% was obtained, which means that its has many deficiencies in the completeness of ISO 9001:2015 documents. The design also includes updating documents such as the organizational structure and quality plan. The results of document creation and updating resulted in a final gap analysis of 73%. Increased gap analysis can be a reference for company to provide human resources who are responsible for carrying out draft documents and required good top management commitment.